O processo de aquisição da autonomia em crianças pré-escolares: uma visão da Psicologia Analítica - Medeiros, Ana Carolina Takenaka (2015)
Autonomy is an important feature in human development, as it enables us to achieve new skills and propel us into increasingly complex levels of behavior. Since most of the current research has focused the development of autonomy during adolescence, this dissertation aimed to study the process of acquisition of autonomy for preschool children. The survey was conducted with mothers of 71 children with ages between 3 and 5 years old, through the Child Behavior Checklist (CBCL/1½ -5) and a questionnaire to assess the perception of autonomy that mothers perceive in their children and also a sociodemographic questionnaire. The method used was quantitative, through convenience sample and the theoretical framework was the Analytical Psychology. Results indicate that children in this age group have good level of autonomy. There was a statistic relevant difference between autonomy of children who have siblings versus children who have no siblings, pointing out that the presence of siblings increases autonomy in children. However, contrary to what was thought initially, there was no statistic relevant difference between genders, between working mothers and housewives or between children who are assisted by nannies and children who are not assisted by nannies. These findings corroborate with the current scientific literature that understands autonomy as intrinsic and inherent to human development